2013
DOI: 10.1007/s11103-013-0149-6
|View full text |Cite
|
Sign up to set email alerts
|

CEBiP is the major chitin oligomer-binding protein in rice and plays a main role in the perception of chitin oligomers

Abstract: CEBiP, a plasma membrane-localized glycoprotein of rice, directly binds with chitin elicitors (CE), and has been identified as a receptor for CE by using CEBiP-RNAi rice cells. To further clarify the function of CEBiP, we produced CEBiP-disrupted rice plants by applying an efficient Agrobacterium-mediated gene-targeting system based on homologous recombination, which has recently been developed for rice. Homologous recombination occurred at the CEBiP locus in ~0.5 % of the positive/negative selected calli. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 34 publications
1
72
0
1
Order By: Relevance
“…The receptors that bind chitin oligomers and induce pathogen defenses in rice (Oryza sativa) and Arabidopsis (Arabidopsis thaliana) also have been identified (Wan et al, 2012;Tanaka et al, 2013;Kouzai et al, 2014). However, to our knowledge, there has been no previous report that chitinases may be involved in eliciting plant defenses.…”
Section: Discussionmentioning
confidence: 99%
“…The receptors that bind chitin oligomers and induce pathogen defenses in rice (Oryza sativa) and Arabidopsis (Arabidopsis thaliana) also have been identified (Wan et al, 2012;Tanaka et al, 2013;Kouzai et al, 2014). However, to our knowledge, there has been no previous report that chitinases may be involved in eliciting plant defenses.…”
Section: Discussionmentioning
confidence: 99%
“…CEBiP is typical receptor-like protein (RLP) with an extracellular domain containing two predicted lysin motifs (LysMs) at the N terminus and a short membrane-spanning domain at the C terminus and lacks cytoplasmic kinase domain but directly involved in chitin-triggered immunity (Kouzai et al 2014). …”
Section: Resistance and Signalling In Plantsmentioning
confidence: 99%
“…OsCEBiP and OsCERK1 were shown to form a receptor complex ligand dependently, which seems to trigger downstream signaling. Knockdown/ knockout of OsCEBiP coupled with affinity labeling experiments showed that OsCEBiP is the major receptor for chitin oligosaccharides in rice, whereas OsCERK1 did not bind chitin oligosaccharides or colloidal chitin [14,17,18]. Epitope mapping by NMR spectroscopy combined with molecular modeling/docking studies and binding studies indicated that two molecules of OsCEBiP simultaneously bind to one chitin oligosaccharide from the opposite surface, interacting with N-acetyl groups in the internal GlcNAc residues, and form a homo-dimer ( Figure 2a) [19 ].…”
Section: Chitin Receptors and Their Activationmentioning
confidence: 99%
“…However, as the knockout of OsCEBiP resulted in the disappearance of most chitin oligosaccharide binding proteins in the plasma membrane and also chitin-induced defense responses [18], it is not clear to what degree OsLYP4 and OsLYP6 contribute to chitin signaling in rice.…”
Section: Current Opinion In Plant Biologymentioning
confidence: 99%
See 1 more Smart Citation